Simulation-driven design of compact ultra-wideband antenna structures. Issue 4 (13th June 2016) - Koziel, Slawomir; Bekasiewicz, Adrian
Abstract : Purpose: – The purpose of this paper is to investigate strategies and algorithms for expedited design optimization and explicit size reduction of compact ultra-wideband (UWB) antennas. Design/methodology/approach: – Formulation of the compact antenna design problem aiming at explicit size reduction while maintaining acceptable electrical performance is presented. Algorithmic frameworks are described suitable for handling various design situations and involving simulation models without and with response gradients available. Numerical and experimental case studies are provided demonstrating feasibility of solving real-world miniaturized antenna design tasks. Findings: – It is possible, through appropriate combination of the global and local optimization methods, surrogate modeling techniques and response correction methods, to find optimum dimensions of antenna structures that minimize antenna size while maintaining acceptable electrical performance. Design optimization can be performed at practically feasible computational costs. Research limitations/implications: – The study summarizes recent advances in miniaturization-oriented design optimization of UWB antennas. The presented techniques reach far beyond the commonly used design approaches based on parameter sweeps and similar hands-on methods, particularly in terms of automation, reliability, and reduction of the computational costs of the design processes. Originality/value: – The proposed design problem formulation and algorithmic frameworks proved useful for rapid design of compact UWB antenna structures, which is extremely challenging when using conventional methods. To the knowledge, this is the first attempt to efficient solving of this type of design problems, especially in the context of explicit antenna size reduction.